Methanogenic potential and microbial community of anaerobic batch reactors at different ethylamine/sulfate ratios - Vich, D. V.; Garcia, Marcelo Loureiro [UNESP]; Varesche, M. B. A. (Brazilian Society of Chemical Engineering, 2011)
Methylamine and sulfate are compounds commonly found in wastewaters. This study aimed to determine the methanogenic potential of anaerobic reactors containing these compounds and to correlate it with their microbial communities. Batch experiments were performed at different methylamine/sulfate ratios of 0.71, 1.26 and 2.18 (with respect to mass concentration). Control and experimental runs were inoculated with fragmented granular sludge. The maximum specific methane formation rates were approximately 2.3 mmol CH4 L-1 g TVS-1 day-1 for all conditions containing methylamine, regardless of sulfate addition. At the end of the experiment, total ammonium-N and methane formation were proportional to the initial concentrations of methylamine. In the presence of methylamine and sulfate, Firmicutes (46%), Deferribacteres (13%) and Proteobacteria (12%) were the predominant phyla of the Bacteria domain, while Spirochaetes (40%), Deferribacteres (17%) and Bacteroidetes (16%) predominated in the presence of methylamine only. There was no competition for methylamine between sulfate-reducing bacteria and methanogenic archaea.
Keywords: Anaerobic process; Methylamine; Sulfate reduction; Methane formation; Microbial community